Indirect Measurement of Streptokinase Concentration in the Plasma of Patients Undergoing Fibrinolytic Treatment - Martin, M (Thrombosis and Haemostasis, 1974)
A new method of determining streptokinase concentrations on a quantitative basis in the plasma of patients undergoing streptokinase infusion is demonstrated. The principle of this method is based on the clot lysis time recorded by the thrombo-elastograph. The test clot constituents were bovine fibrin, bovine plasminogen, human euglobulin, EDTA, human plasma (with unknown streptokinase quantity) and thrombin. As plasminogen (euglobulin) and fibrinogen were present in the test coagulum in rather high concentrations (fixed excess) no interference with changing plasminogen and fibrinogen levels of the patient’s plasma was observed. Further, due to high EDTA concentrations, no interaction with platelet functions and coagulation factors took place. The standard error of measuring 5 u of streptokinase in one ml of human plasma was determined at s = ±0.47 u/ml.Eleven patients undergoing fibrinolytic treatment with streptokinase were monitored by streptokinase determination in the plasma. In this group of patients, streptokinase concentration values varying between 15 and 0.5 units/ml plasma were measured. One striking feature was the continuous decrease in streptokinase concentration in the plasma, in spite of unchanged streptokinase infusion rates. This observation was consistent in regimens with both large (100,000 u/h) and small (30,000 u/h) streptokinase infusion rates. No explanation is available for this observation up to now. A rise in circulating anti-streptokinase contents was precluded. Possibly, an accelerated streptokinase metabolism rate in the course of long-term streptokinase administration may be involved.